Los epígrafes delatores - Butti, Enrique (Universidad Nacional del Litoral, 2019)
This article configures an investigation on the extent and effects of the epigraphs in some of Edgar Allan Poe’s tales. Thus, it will focus on how the epigraphs operate in order to anticipate the conclusion of a given storyline and how these paratexts encompass a particular interpretation.